Is the intergenerational war real? An analysis of intergenerational differences in the willingness to pay for child welfare services and welfare services for the elderly in Korea. (3rd July 2019) - Kim, Hyun Joon; Kim, Na Yeon
ABSTRACT: Do intergenerational conflicts exist across welfare service provision between old and young generations? By using multinomial logit regression on citizens' willingness to pay for elderly and child welfare services, the authors confirm that older generations prefer services that directly benefit themselves but find little evidence that older generations are less willing to pay additional taxes to fund child welfare services. This paper emphasizes interdependence in welfare service areas and urges the government to improve the capacity to deliver welfare services effectively.